A Realist Evaluation of a “Whole Health” Response to Domestic Violence and Abuse in the UK - Kelly Buckley (Violence Against Women, 2024)
Health Pathfinder is a multilevel system change intervention initiated to transform the health response to domestic violence and abuse in eight sites in England. The current study drew upon interviews with health professionals (n=27) and victim-survivors (n=20) to provide a realist account of how this intervention achieved its goals. Findings show that five change mechanisms explain why Health Pathfinder was effective as an ecological intervention: awareness, expertise, relationships, empowerment and evidence. Positive progress in respect of each mechanism had meaningful impacts on victim-survivor experiences of enquiry, disclosure and uptake of services, and had the potential to meaningfully impact health inequities.